Validity of E-Inquiry-Based Practical Instructions to Improve Critical Thinking in Plant Anatomy Learning - Khafidhotur Rohmah; Imas Cintamulya (Department of Biology Education UIN Sunan Gunung Djati Bandung, 2025)
The development of technology is currently accelerating. One of the uses of technology in education is teaching or supporting media in learning. This study aimed to design E-instructions for the stomata observation practicum inquiry method to improve critical thinking in learning valid plant anatomy and to determine E-instructions' validity to improve critical thinking in learning plant anatomy. The method in this research is the ADDIE method, which has several stages: analysis, design, development, implementation, and evaluation. This research data was collected using validity instruments in the form of validity sheets. This research uses a descriptive quantitative data analysis technique describing the data's validity. The validity test results get the following average: the material aspect receives an average of 85.8%, the systematic aspect gets a validity value of 84.3%, the language aspect gets a value of 88.3%, and the graphic aspect receives a value of 89.3%. The average score for all aspects of the assessment is 86.9%. Based on the scores of the three expert validators, it can be concluded that the results of the validation of the Inquiry-Approach Practicum E-Instructions to Improve Critical Thinking in Plant Anatomy Learning are in the very valid category.